Potentialités et limites des curricula de SVT : quelles contributions des questions environnementales pour une éducation au politique ? - Malou Delplancke; Hanaà Chalak (Éducation et Socialisation)
The central issue of this article is to characterize the conditions of a scientific education which allows to take in charge the double political and scientific dimension of environmental questions (EQ). Our reflection is based on an analysis of the curricula, carried by the new programs and the textbooks of life and earth sciences and Scientific Education, specifically on the environmental themes. Our analyses show that the way in which the EQ are carried out focuses on technology as a source of solutions to human problems, participates in a positivist conception of science, and relies on an anthropocentric approach. The programs and textbooks implicitly transmit a relationship to the world that is very much rooted in the paradigm of modernity. We discuss the possible levers for re-politicizing these questions in the classroom, by means of their (re)problematization in a context of instability of knowledge, of fuzzy problems, in order to contribute to a citizen’s education able to respond to the challenges of the anthropocene.